AI-Powered Approaches for Sustainable Environmental Education in the Digital Age: A Study of Chongqing International Kindergarten - Arif, Muhammad; Ismail, Aneta; Irfan, Sadia (International Journal of Environment, Engineering and Education, 2025)
The integration of technology into education has garnered significant interest, particularly in its potential to support environmental sustainability. This exploratory research investigates the role of artificial intelligence (AI) in early childhood education, with a focus on its implementation at Chongqing International Kindergarten to teach sustainability concepts. Guided by Mezirow’s Theory of Transformative Learning and Goleman’s concept of Ecological Intelligence, the study explores how AI-powered tools—including virtual ecosystems, real-time feedback systems, and eco-conscious behavior tracking mechanisms—enhance critical reflection, foster ecological intelligence, and promote environmentally responsible behaviors among young learners. A qualitative case study approach was employed, incorporating classroom observations, educator interviews, and pre-and post-assessments to evaluate engagement, environmental awareness, and behavioral changes. The findings reveal that AI tools significantly enhance environmental literacy, helping children understand the consequences of their actions and encouraging them to adopt sustainable practices. Interactive and personalized learning experiences AI provides stimulate critical thinking, transform sustainability-related values, and foster a deeper understanding of ecological interconnections. Students demonstrated improved awareness of sustainability concepts, such as resource conservation and biodiversity, alongside increased engagement in eco-friendly behaviors, including recycling and energy conservation. This research highlights the transformative potential of AI in early education, demonstrating its capacity to influence children's attitudes and behaviors toward environmental responsibility. Integrating AI-driven educational tools into sustainability curricula is crucial for cultivating a generation capable of making informed environmental decisions. The study concludes by recommending further exploration of AI's role in early education to optimize its impact on fostering long-term ecological intelligence and transformative learning.